Performance Comparison of Waste Management Approach in West Java through Masaro and Waste-to-Energy (WtE) Power Plant Technologies - Abidin, A. Zainal; Steven, Soen; Silitonga, Andreas B. A.; Christian, Axel A.; Suyadi , Malikul M. A.; Soekotjo, Ernie S. A.; Yemensia, Elsye V.; Matin , Alex; Putra, Ridwan P. (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2025)
Waste is often considered as something useless and valueless. However, as the world enters a new industrial era, there is a growing awareness that waste has a high economic value. With proper processing, the waste can be recycled and even used as a feedstock for power generators. With a waste production reaching 24,000 tons per day in West Java, waste becomes a sustainable raw material. There are several methods for processing waste, such as Zero Waste Management Technology (Masaro) and Waste-to-Energy Power Plant (WtE). This study aims to compare the performance of Masaro and WtE technologies from their potential and economic impact. Both methods certainly have their advantages and disadvantages in terms of waste reduction capacities, products obtained, and financial benefits. This study reveals that Masaro technology can reduce 100% waste, whereas WtE can only reduce up to 70–97%. Subsequently, Masaro technology offers more diverse products rather than WtE (6 products vs. 3 products). Moreover, the gross profit margin (GPM) shows that Masaro can reach 99.27% while WtE is still in the range of 12.23–25.30%. It can be concluded that Masaro has quite higher potential and economic benefits compared to WtE.